Assessing anaerobic microbial degradation rates of crude light oil with reverse stable isotope labelling and community analysis - Beilig, Sebastian; Pannekens, Mark; Voskuhl, Lisa; Meckenstock, Rainer U. (Frontiers in Microbiomes, 2024)
Oil reservoirs represent extreme environments where anaerobic degradation profoundly influences oil composition and quality. Despite the common observation of biodegraded oil, the microbial degradation rates remain largely unknown. To address this knowledge gap, we conducted microcosm incubations with light oil as carbon source, original formation water and sulfate as electron acceptor, closely mimicking in situ conditions to assess oil degradation rates. Samples were taken from a newly drilled oil well to exclude contamination with injection water and allochthonous microorganisms. At the end of the incubations, microbial community analyses with 16S rRNA amplicon sequencing revealed the most prominent phyla as Desulfobacterota, Thermotogota, Bacteroidota, Bacillota (formerly Firmicutes), and Synergistota, collectively accounting for up to 44 % of relative abundance. Ion chromatography and reverse stable isotope labelling were used to monitor sulfate reduction and CO2 evolution respectively. We calculated an average degradation rate of 1.23 µmol CO2 per gram of light oil and day corresponding to 15.2 mmol CO2/mol CH2(oil) per year. This resembles to approximately 200 years to degrade one gram of oil under the applied, presumably ideal conditions. Factoring in the available oil-watercontact (OWC) zone within the incubations yielded a degradation rate of 120 g CH2 m -2 OWC per year, closely aligning with the modeled degradation rates typically observed in oil reservoirs (Head et al., 2003, Larter et al., 2006). Moreover, our study highlighted the utility of the reverse stable isotope labeling (RSIL) approach for measuring complex substrate degradation at minute rates.